Attack of apollyon - Jenkins, Jerry B.; Fabry, Chris, 1961-; LaHaye, Tim F. (Wheaton, Ill. : Tyndale Kids, 2002)
The young Tribulation Force, a group of teens left behind on Earth after God's Rapture, braces to face the next judgment--one so terrible it will be announced from heaven first.
"Revenge of the locusts"--Cover.
5.9
5-8
Keywords: Eschatology -- Fiction; Fantasy; Teenagers -- Fiction; Eschatology -- Fiction; Teenagers -- Fiction; Fantastic fiction